Effect of Trichoderma viride on activities of polygalacturonase of Rhizoctonia - LIU Kai-qi; XIANG Mei-mei; LIU Ren; ZENG Yong-san; YANG Yong; YU Jin-feng; JIANG Xin-yin; ZHANG Yue-li (浙江大学学报. 农业与生命科学版)
The pectin is a backbone of the plant cell wall, its network structure will systemicly resolve when the plant cell splits up and forms. The pectinase produced by Rhizoctonia mainly acts on the pectin of cell wall, and causes the maceration of tissue and the death of protoplast. Polygalacturonase (PG) can decompose the galacturonic acid of disease tissue.The research defined the PG activities of extracellular metabolite of the different virulence Rhizoctonia isolates, and testifid the effect of Trichoderma viride to PG activities, and clarified the mechanisms of biocontrol by Trichoderma.The test methods as following: Firstly, to select the isolates of different virulence: WK-47, WK-141 and WK-160 strain of Rhizoctonia AG-D and YW-2 strain of Rhizoctonia AG1-IA and TCS-1 strain of Trichoderma viride. Secondly, to culture TCS-1 on PD, and draw a group of fermented liquid in every 24 hours, and draw 7 times. Thirdly, to culture quietly Rhizoctonia isolates with Czapek-Dox at 25 ℃ for 15 days, filter and centrifuge (2350 g × 30 min), fetch the clear liquid, put it into the ammonium sulfate according to 60% saturation degree, put it quietly for 30 min at 4 ℃, centrifuge (21000 g × 30 min) at 4 ℃, remove the clear liquid, dissolve the deposit with sodium acetate buffer (25 mmol/L, pH5.5), dialysis for 48 h in the same buffer, and change the buffer every 12 h, Fourthly, to put TCS-1 fermented broth of different times in the tubes, one mL per a tube, add 0.5 mL PG to every tube, react for 4 h in 30 ℃ water, the same time fetch the test tube filled with the same treated liquid that was not dealed in 30 ℃ water. Finally, to testify PG activities with DNS's test.In all, PG of Rhizoctonia had high activities and virulence. The conrtrol efficacy of T. viride to PG activities of WK-47, WK-141, WK-160 and YW-2 were 95%, 94%, 95%, 92% separately, fermented time had a great influence to control efficacy, the third fermented broth did the best. Through effect to PG activities T. viride can reduce the virulence of Rhizoctonia, and protect the hosts. The specific mechanism, qualitative and quantitative research of antagonistic substance in the fermented broth will be further carried out.